Mendicity. - (:unkn) unknown (My University, 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Begging; Great Britain -- Social conditions -- 19th century -- Caricatures and cartoons